A study on the factors contribute to the population growth in Malaysia at Social Services Section, Economic Planning Unit, Prime Minister's Department / Syukriyani Shudim - Shudim, Syukriyani (2014)
The Economic Planning Unit (EPU) is an important sector in the Malaysian economy in the monitoring of national economic performance and social development. The population growth is one of the social developments in Malaysia. In this study, the researcher was using secondary data. The effectiveness and accuracy of the fertility rate, the mortality rate and the life expectancy variables will be examined. The model that used to examine is econometric modelling. The selection of the best model based on the results that fulfill the characteristic of no serial correlation, high goodness of fit, less p-value, and no existence of multicollinearity. According to those characteristic, variable of the fertility rate and the life expectancy should be dropped. Log transformation should be performed towards variable of the mortality rate in order to increase their normality characteristic. The final model that consider as the best model is a model with log transformation towards mortality rate and lag of dependent variable, the population growth with one degree